Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1155/2019/2165918
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Synovial Macrophage Pyroptosis Alleviates Synovitis and Fibrosis in Knee Osteoarthritis

Abstract: Increasing evidence has shown that macrophage pyroptosis in different tissues participates in chronic aseptic inflammation and is related to tissue fibrosis. Our last studies also revealed the vital role of synovial fibroblast pyroptosis in the onset and development of knee osteoarthritis (KOA). In this study, we aimed to investigate whether synovial macrophage pyroptosis did occur and whether this form of cell death should be related to synovitis and fibrosis of KOA. In the synovial tissue of KOA model rats, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 34 publications
5
79
0
Order By: Relevance
“…A total of 4376 abstracts were screened, and 168 articles were selected for full‐text article screening (Figure 1). After full‐text article screening, 66 articles were included in the systematic review as they fulfilled all selection criteria 13,15,23‐27,32‐91 . Although most studies focused on either human musculoskeletal disease (n = 31) or animal models of musculoskeletal disease (n = 31), four studies investigated HMGB1 in both human and animal models of musculoskeletal disease (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 4376 abstracts were screened, and 168 articles were selected for full‐text article screening (Figure 1). After full‐text article screening, 66 articles were included in the systematic review as they fulfilled all selection criteria 13,15,23‐27,32‐91 . Although most studies focused on either human musculoskeletal disease (n = 31) or animal models of musculoskeletal disease (n = 31), four studies investigated HMGB1 in both human and animal models of musculoskeletal disease (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…HMGB1 expression was increased in animal models of musculoskeletal disease in 22 of 23 studies (Table 3). 13,37,40,44,45,47‐52,54‐56,60,61,63,67,70,83,84,87 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researches confirmed that the studies of NLRP3-mediated chronic aseptic inflammation are becoming increasingly popular, and evidence of NLRP3 activation has also been found in KOA. 41 The downstream IL-1β and IL-18 have been highly correlated with OA pain. Our research have indicated that NLRP3 may be the effect target of Chrysin, which can effectively attenuate the NLRP3 inflammasome cascade, which is consistent with the various antiinflammatory effects of Chrysin confirmed by other scholars.…”
Section: Discussionmentioning
confidence: 99%